Nutritional and social hierarchy establishment of the primitively eusocial wasp Mischocyttarus cassununga (Hymenoptera, Vespidae, Mischocyttarini) and related aspects - Murakami, André Sunao Nishiuchi [UNESP]; Shima, Sulene Noriko [UNESP] (My University, 2006)
The results on the nutritional influence in the social hierarchy establishment among females from six colonies of Mischocyttarus cassununga show that: - there was no caste determination in the pre-imaginal period concerning ingested food quantities, however, in relation to qualification (proteins and carbohydrate) the Mann-Whitney test applied showed variation among colonies: in two colonics (colony 3, p=0.0209; colony 4, p=0.0090) the larvae which ingested a higher quantity of solid food became adults of hierarchically higher position, however in two other colonies, colony 1 (p=0.6744) and colony 2 (p=0.3367) this difference was not statistically significant; in two experimentally manipulated colonies the caste determination was observed in the imaginal phase (it was verified that the larger the food quantity consumed, the higher the assumed hierarchical position by the individuals); - adult individuals of hierarchically higher position in two colonies ingested a greater amount of solid than liquid food (Mann-Whitney; p ≤ 0.05), however in the other three colonies there was no difference. It can be seen that for all colonies (2, 3, 4, 5 and 6) the high tendency to solid food ingestion occurs. In colony 1, this data was not collected because the observation purpose was different); - inside the colony hierarchy, the older individuals were the ones that occupied higher hierarchical positions; - more than one inseminated female per colony was found in the two experimentally manipulated colonies ; - ovarian development is greater in inseminated females; - the average height of the 3rd tergite was greater for inseminated females, indicating an adaptation to accommodate larger ovary development (t-Student test; p ≤ 0.05).
Keywords: Hierarchy establishment; Mischocyttarini; Mischocyttarus cassununga; Primitively eusocial wasps; Vespidae; Hymenoptera